M13 Bacteriophage as Materials for Amplified Surface Enhanced Raman Scattering Protein Sensing. (6th December 2013) - Lee, Ju Hun; Xu, Phyllis F.; Domaille, Dylan W.; Choi, Chulmin; Jin, Sungho; Cha, Jennifer N.
<x xml:space="preserve">Abstract</x> Because of their unique properties, nanomaterials have been actively investigated in recent years for biosensing applications. A typical approach for biomarker detection is to attach capture or detection antibodies to nanomaterials, allow the analyte to bind, and measure the resulting change in signal. While antibodies or aptamers possess at most one binding site each for the nanomaterial and analyte, it is shown that the high surface area filamentous M13 bacteriophage can be utilized as a scaffold for generating an amplified signal. Since only a few proteins at the tip of the micrometer‐long virus are involved in antigen binding, the rest of the bacteriophage can be augmented with hundreds of functional groups, each of which can bind to a specific nanomaterial. It is demonstrated that the combination of DNA‐modified M13 bacteriophage and surface enhanced Raman spectroscopy (SERS) active nanoparticles can be used to produce exponential gains in Raman signal compared to that of antibodies at the same antigen concentration. Because of these high sensitivities, Raman measurements can be made directly from individual silica microparticles, potentially enabling future single step identification and analysis of different proteins in complex mixtures, while avoiding additional processing steps or prepatterned microarrays.